OP0151 A Study on Medical Students Learning Ultrasound in Rheumatoid Arthritis (ASMSLURA). (15th July 2016) - Sukhdeo, A.; Joshua, F.; Damodaran, A.; Shulruf, B.
Abstract : Background: Rheumatoid arthritis (RA) affects ∼ 0.5% of the adult population worldwide. The current "standard" of teaching consists of didactic lectures and bedside teaching. It has been shown that musculoskeletal teaching is inadequate and needs improvement. 1–3 Ultrasound is safe and increasingly taught to postgraduates in specialties such as rheumatology and orthopaedics to improve their clinical skills. Literature suggests that ultrasound teaching may be beneficial for medical students. 4 Objectives: This study aimed to assess whether the incorporation of ultrasound in teaching improved medical students' knowledge of rheumatoid arthritis and interest in musculoskeletal medicine. Methods: This study was a single site, randomised, prospective, open, cross over trial comparing RA teaching in medical students, assisted with ultrasound, versus teaching via standard methods. The study included 3rd and 4th year students enrolled in the University of New South Wales 6 year undergraduate medical program. Students were randomised into 2 groups, and underwent both sets of teaching in different order. A written multiple-choice exam, was held before any teaching began, and after the first and second sets of teaching. An evaluation survey was administered at the conclusion of the two sets of teaching. Results from the MCQ exam was statistically analysed and the survey was qualitatively analysed. Results: A total of 20 students completed the study (11 students from group 1 and 9 from group 2). The exam scores improved significantly (p≤0.01) for both groups after they undertook standard teaching. However, the exam scores did not improve for either group after ultrasound teaching. We also found that exam scores improved significantly (p≤0.01) for both groups at the conclusion of the entire teaching period. The order in which the students underwent teaching did not result in significantly different scores. The questionnaire revealed that most students thought ultrasound was of educational value and helped them improve their knowledge of anatomy. However they were equivocal about whether it helped their learning of RA. Both groups rated standard teaching highly. Conclusions: This crossover trial demonstrates significant improvement in students' knowledge of RA after undergoing standard teaching as opposed to ultrasound teaching. Factors which may have contributed to this result and which deserve further exploration include using different assessment methods for ultrasound teaching, using different learning levels and using different teachers. References: Doherty, M., Abawi, J., & Pattrick, M. (1990). Audit of medical inpatient examination: A cry from the joint. Journal of the Royal College of Physicians of London, 24(2), 115–118. Ahern, M. J., Soden, M., Schultz, D., & Clark, M. (1991). The musculo-skeletal examination: A neglected clinical skill. Australian & New Zealand Journal of Medicine, 21(3), 303–306. Spencer MA, Dixon AS. Rheumatological features of patients admitted as emergencies to acute general medical wards. Rheumatology and rehabilitation 1981;20:71–3. Wright SA, Bell AL. Enhancement of undergraduate rheumatology teaching through the use of musculoskeletal ultrasound. Rheumatology 2008;47:1564–6 Disclosure of Interest: None declared